Getaway : food & drink to transport you - Erickson, Renee; Dickerman, Sara, 1971- (Abrams, 2021)
"Acclaimed chef, restaurateur, and artist Renee Erickson invites you on a culinary journey via her favorite places in the world- Rome, Paris, Normandy, Baja California, London, and her hometown, Seattle. Equally aspirational travelogue and practical guide to cooking at home, the book offers 120 recipes and 60 cocktail recipes for simple meals that evoke the dreamiest places and cuisines. From not-too-intricate cocktails and snacks to effortless entrees, these are the recipes that inspire Erickson and make for relaxed, convivial evenings, whether at home or abroad. Showcasing Erickson's appealing and high-style aesthetic and featuring gorgeous photography and hand-drawn illustrations, this book offers a richly visual survey of beautiful, easy ways to escape the everyday, with meals that you will want to eat every day."--Publisher's website.